2022
DOI: 10.1371/journal.pone.0265514
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of factors affecting wildlife survival during rehabilitation and release

Abstract: Millions of native animals around the world are rescued and rehabilitated each year by wildlife rehabilitators. Triage and rehabilitation protocols need to be robust and evidence-based, with outcomes consistently recorded, to promote animal welfare and better understand predictors of wildlife survival. We conducted a global systematic review and meta-analysis of 112 articles that reported survival rates of native mammals and birds during rehabilitation and after release to determine intrinsic and extrinsic fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 92 publications
2
57
0
Order By: Relevance
“…Our study found an annual survival rate of 58.5%, comparable to survival rates of other rehabilitated koalas (e.g., 58% survival 43 ), but lower than some wild living populations (e.g., 92.5–74% survival 77 ) which indicates that techniques for improving outcomes for koalas in care are much needed. We discuss a range of recommendations below, which contribute to the identified need for evidence-based and context specific protocols to maximise outcomes for rehabilitated animals 78 . We found that including basic assessments that don’t require any specialist equipment (e.g., body condition and climbing ability scores) can improve post-release survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found an annual survival rate of 58.5%, comparable to survival rates of other rehabilitated koalas (e.g., 58% survival 43 ), but lower than some wild living populations (e.g., 92.5–74% survival 77 ) which indicates that techniques for improving outcomes for koalas in care are much needed. We discuss a range of recommendations below, which contribute to the identified need for evidence-based and context specific protocols to maximise outcomes for rehabilitated animals 78 . We found that including basic assessments that don’t require any specialist equipment (e.g., body condition and climbing ability scores) can improve post-release survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identi ed several critical areas where rehabilitation and release procedures can be improved, which are easily implemented and applicable to a range of different species. We discuss a range of recommendations below, which contribute to the identi ed need for evidence-based and context speci c protocols to maximise outcomes for rehabilitated animals 72 . We found that including basic assessments that don't require any specialist equipment (e.g., body condition and climbing ability scores) can improve post-release survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is known that male sparrowhawks were less likely to be released than females [ 17 ], and that male raptors are more susceptible to spontaneous mortality than females [ 73 ]. Factors influencing survival rates before and after revival have been reviewed by Cope et al [ 74 ] and should be used as a framework to guide rescue and treatment protocols, tailored to each species and based on global evidence of effectiveness. With these robust protocols in place, veterinarians and rescue organizations can continue to minimize animal suffering and maximize the effectiveness of rehabilitation programs in an increasingly anthropogenically expanding world with increasing climate change [ 74 ].…”
Section: Discussionmentioning
confidence: 99%